Numerical analysis of aluminium oxide and silicon dioxide nanofluids in serpentine cooling plate of PEMFC - Amira Shahirah, Malek Amir Azmin; Irnie Azlin, Zakaria; Saifuddin, Khalid; Wan Azmi, Wan Hamzah; Wan Ahmad Najmi, Wan Mohamed (Akademi Baru, 2020)
Proton Exchange Membrane Fuel Cell (PEMFC) is an alternative energy application for vehicular power sources and is a strong contender for clean and efficient power generation. However, the heat generated by the PEMFC need to be taken care of efficiently as to avoid damage to fuel cell component especially membrane due to overheat. Excessive heat can also lead to performance deterioration of PEMFC. In this study, the heat transfer performance of Aluminium Oxide (Al2O3) and Silicon Dioxide (SiO2) in water with low concentration value of 0.1 %, 0.3 % and 0.5 % volume were adopted as cooling medium in PEMFC. The simulation software used was ANSYS Fluent in laminar flow condition. The nanofluids studied were applied in a carbon graphite serpentine cooling plate of PEMFC which was subjected to a constant heat flux of 300 W. The heat flux mimicked the heat received during actual reaction in PEMFC. The result shows that maximum improvement was at 2.14 % improvement in Al2O3and 1.15 % improvement in SiO2in term of heat transfer coefficient of 0.5 % volume concentration as compared to water. This is due to the superior thermal conductivity of nanofluids as compared to base fluid. The improved Brownian motion has enabled such excellent heat transfer. However, the improvement was also accompanied by the pressure drop increment as compared to base fluid water.